Gleisdreick / Park. Life Berlin. - (:unkn) unknown (transcript, 2015)
Was zeichnet den Park des 21. Jahrhunderts aus? Wie muss Berlin künftig mit urbanem Freiraum umgehen? In Interviews mit Künstlern, Freiraumexperten und Berlinern wird die Entwicklung des ehemaligen Güter- und Passagierbahnhofs portraitiert: von einem geschichtsträchtigen Brachland, das zwischen Ost und West verloren schien, zu Berlins beliebtestem öffentlichen Park. In zahlreichen Bildern und Statements trägt das bilinguale Buch zum zeitgenössischen Diskurs zur Stadtentwicklung, zu bürgerlichem Engagement und zur Frage nach den Bedürfnissen der modernen Stadtgesellschaft bei.

By drawing together widely dispersed yet central writings, the Berlin Reader is an essential resource for everyone interested in urban development in one of the most interesting and important metropolises in Europe. It provides scholars as well as students, journalists and visitors with an overview of the most central discussions on the tremendous changes Berlin experienced since the fall of the wall. It covers a wide range of issues, including inner city renewal, housing and the local economy, gentrification and other urban conflicts. The book breaks ground in two dimensions: first, by offering also non-German speakers an insight into the very controversial debates after reunification, and, second, by highlighting the ambivalent consequences of Berlin's urban transformation in the past decades.
Keywords: Freizeit; Park; Öffentlicher Raum; Freiraum; Lebensqualität; Institutionengeschichte; Stadtgestaltung; Befragung; Entstehungsgeschichte; Bürgerengagement; Stadtgesellschaft